UMP, Sapura seal JV in human capital development - UMP, PNC
Universiti Malaysia Pahang (UMP) sealed a joint venture (JV) with automotive components and spare parts manufacturer, Sapura Industrial Bhd (SIB), to enhance the two-party collaboration on human capital development, when it signed a Memorandum of Agreement (MoA) in Bandar Baru Bangi, Selangor, last November.